Opening third spaces for research in education : challenging the limits of technocratic methods - Blakely, Erin, 1978-; Hemphill, David (Myers Education Press, 2021)
Opening Third Spaces for Research in Education challenges dominant educational research methods. It rejects the reductive binaries normalized in social science research--theory/practice, objective/subjective, quantitative/qualitative. Drawing from multiple fields and eras, the book opens third spaces between these artificial poles to help researchers expand interpretations and possibilities for research. Critiquing the current focus on the measurement of ""student learning outcomes"" and high-stakes assessment, the book offers conceptual tools and case examples to support educators in reconcept.